Behavior Analysis of Deformation Changes After Sagging on The Telaga Abadi Suspension Bridge - Aco Wahyudi Efendi (Civil Engineering Dept, Balikpapan State Polytechnics, 2022)
The occurrence of changes in the location and height of the tide at the time of execution that exceed the planning conditions and disrupt the flow of municipal shipping. For this reason, the suspension bridge chamber was upgraded in order to create a traffic-free area opposite the free threshold. The results of the manual analysis taking into account the labor force due to the bridge steps, so that the real value of the bridge chamber is obtained to obtain the ideal deformation of the bridge working load. The ability of the bridge state to change the deformation results from this evaluation. The behavior of the four conditions was significantly different, namely the SDL forward state, in which the horizontal force that occurred in this state increased, but the deflection decreased by up to 200%, whereby in the f0 forward state was 0.16 meters , but in the SDL forward state the horizontal force only increased with a deflection of 0.05 meters. However, the overall result is that the stress states that occur are still below the limit or permissible conditions, based on the stress-strain curve of the cable material, the stress under operating conditions is still in the elastic range of the material.